Drought and frost resistance vary between evergreen and deciduous Atlantic Forest canopy trees - Di Francescantonio, Débora (2020)
Frost and drought are key stress factors limiting the growth and distribution of tree species. Resistance to stress involves energy costs that may result in trade-offs between different functional traits. Structures or mechanisms that can help to withstand stress imply differences in the carbon economy of the species. Although adaptive responses to frost and drought resistance are usually of a similar nature, they are rarely assessed simultaneously. We investigated these resistance mechanisms in 10 canopy tree species coexisting in the semi-deciduous subtropical forests of northern Argentina. We measured leaf lifespan, anatomical, photosynthetic and water relations traits and performed a thermal analysis in leaves to determined ice nucleation and tissue damage temperatures. Our results showed that evergreen and deciduous species have different adaptive responses to cope with freezing temperatures and water deficits. Evergreen species exhibited cold tolerance, while deciduous species were more resistant to hydraulic dysfunction and showed greater water transport efficiency. Further research is needed to elucidate resistance strategies to stress factors at the whole tree-and stand level, and possible links with hydraulic safety and efficiency among different phenological groups. This will allow us to predict the responses of subtropical forest species to changes in environmental conditions under climate change scenarios.